A Novel Algorithm for Detecting Node Clone Attack in Wireless Sensor Networks - Patil, Deepali S.; Patil, Shailaja C. (2017 International Conference on Computing, Communication, Control and Automation (ICCUBEA), 2017)
Dynamically changing, self configuring wireless sensor network consists of sensor nodes often deployed in harsh environment. Because of the unattended nature and lack of tamper resistant hardware, sensor networks are subject to variety of attacks like Sybil, Eavesdropping, Denial of service etc. One of the most dreadful attack is node clone attack, where attacker captures node and extracts its secrete information, makes replicas of it and insert them in the network field for further malicious behaviour. To detect and mitigate such attack, various detection schemes have been proposed based on static and mobile wireless sensor networks. In this paper, a novel node's location speed time based detection algorithm has been proposed, for detecting node clone attack in wireless network. This algorithm helps to reduce the Communication cost, Routing Overhead of the entire network and improves throughput of the network.